When Brazil Got the Blues: The Diffusion of Blues in Brazil - Marcus, Alan P. (Brasiliana: Journal for Brazilian Studies, 2022)
The focus of this article is to understand and examine the phenomenon of the introduction of blues as a musical genre in Brazil (1985-1992), which has never been studied. By highlighting the processes of globalization and the Brazilian blues band from Rio de Janeiro, Blues Etílicos, I ask what were the spaces, places, and venues that helped to disseminate blues throughout Brazil? How does an African-American-based genre adopted and popularized by upper-and-middle-class white urbanites in Brazil? To answer these questions, I examine political, musical, and cultural backdrops, and the end of Brazil’s military dictatorship in 1985, which overlapped with a major Brazilian rock festival, “Rock in Rio,” and Brazil’s first blues festival in Ribeirão Preto in 1989. This article adds to the scholarly literature of blues and music geography by looking at ongoing discussions of Brazil’s changing political, cultural, and musical landscapes.